Impact of Public Infrastructure on Output of U.S. Food Manufacturing Industries: A Heterogeneous Dynamic Panel Approach. Issue 4 (2nd March 2016) - Tong, Tingting; Yu, T. Edward; Jensen, Kimberly; De La Torre Ugarte, Daniel; Cho, Seong‐Hoon
ABSTRACT: This study analyzes the long‐run impacts of public infrastructure on output of 34 U.S. food manufacturing/processing industries during 1958–2000 using heterogeneous dynamic panel methods, including mean group and pooled mean group methods. The results suggest that public infrastructure has a long‐term output impact across U.S. food manufacturing and processing industries. A 1% increase in public infrastructure increases U.S. food manufacturing output by 0.06% in the long run. The long‐run positive impact of public infrastructure on food output suggests its importance to the food manufacturing sector of continuous public infrastructure investment [EconLit citations: Q13; H54; C33].